Consumers' perceptions of the dietary supplement health and education act: implications and recommendations. Issue 3 (2nd November 2015) - Dodge, Tonya
Abstract : In 1994, the United States Congress passed the Dietary Supplement Health and Education Act (DSHEA). The regulatory framework for dietary supplements created by DSHEA has led to significant misperceptions regarding consumers' understanding of the safety and efficacy of supplements. Research shows that consumers erroneously believe that: (1) supplements are approved by the government, (2) supplements have been tested for safety and effectiveness, (3) the content of supplements is analyzed, and (4) manufacturers are required to disclose known adverse effects to consumers. Furthermore, labelling requirements that are intended to provide transparency to consumers are relatively ineffective. The following four recommendations are offered for reforming DSHEA: (1) only allow structure‐function claims that are supported by research evidence, (2) require manufacturers to list known adverse effects on the labels of dietary supplements, (3) require that the Food and Drug Administration analyzes the content of dietary supplements and (4) restrict the definition of dietary ingredients. These recommendations would bring DSHEA to more closely align with consumer expectations regarding the regulation of dietary supplements and would likely provide a safer landscape for the use of supplements. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Two decades after DSHEA was passed, consumers still fail to understand the way in which dietary supplements are regulated. Four recommendations to the DSHEA are offered as a way to more closely align it with the expectations of consumers. These recommendations have the potential to create a safer landscape for consumers who use dietary supplements.